ANALISIS TENTANG PERANAN PEMERINTAH DAN ORANG TUA TERHADAP PERLINDUNGAN ANAK DI TINJAU DARI PERATURAN PERUNDANG-UNDANGAN - Mei Lan Lestari (Fakultas Syariah dan hukum Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
Abstract Humans are the most perfect creatures of Allah among all creatures who are given two powers, the power of thought and power of sense. Man was created as a personal which born with physically and mentally and also has mind and will. Human nature is to grow and develop into a child who must be protected, educated and respected his rights as a human being, because the child is a trusteeship and also a gift given by Almighty God to Parents. In The 1945 Constitution specifically relating to Child Rights contained in Article 28B paragraph (2) states that